EVALUASI PENGENDALIAN INTERNAL ATAS SISTEM INFORMASI AKUNTANSI PENGIRIMAN BARANG PADA PT. TIKI JALUR NUGRAHA EKAKURIR (JNE) AGEN SAMMIHA KOTA PALEMBANG - Triyanto, Agus (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2024)
Shipping information systems involve activities, benefits, or satisfactions offered for sale and provide information related to shipping goods and transaction data within an interconnected process involving senders, all aimed at achieving profitability. The purpose of this research is to determine whether the accounting information system for shipping goods at PT. Tiki Jalur Nugraha Eka kurir, Sammiha agent in Palembang City has been implemented by Standard Operating Procedures (SOP) and internal controls over the shipping information system have been effectively executed. Data was collected through observation, interviews, and documentation. The analytical methods employed included reviewing flowcharts, Standard Operating Procedures (SOP), and internal controls according to COSO guidelines at PT. Tiki Jalur Nugraha Eka kurir, Sammiha agent in Palembang City. The results of the research indicate that the procedures at PT. Tiki Jalur Nugraha Eka kurir has been carried out as intended, but some deviations from Standard Operating Procedures (SOP) were observed. However, weaknesses were identified in the execution of the shipping information system or company SOP, rendering it ineffective. The flowchart diagram serves as a tool to improve the implementation of an efficient and effective shipping information system. It can be concluded from the functioning information system that the shipping process occurs through courier handovers and transfers, revealing common errors.